COORPERATIVE LEARNING METHOD TYOE NUMBERED HEADS TOGETHER (NHT) STUDENTS IN EFFORTS TO MANAGEMENT MARKETING MASTERY IN ECONOMICS FACULTY MUHAMMADIYAH UNIVERSITY OF NORTH - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research aims to enhance the activity of the students in the lecture course marketing management in particular through the implementation of cooperative learning Numbered Heads Together (NHT) and to find out how far the mastery of course material marketing management with the implementation of cooperative learning Numbered Heads Together (NHT).